2023
DOI: 10.1088/1361-6552/acb8a2
|View full text |Cite
|
Sign up to set email alerts
|

Resources on physics education using Arduino

Abstract: In this manuscript, we present a collection of papers, published in different journals, that show the use of the Arduino board in physics. Arduino is used, in most cases, to automate or collect data from experiments in many fields. Here we summarized the manuscripts, by year of publication, field, language, and source, giving to the reader a source of references in the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Although the measurement of the electrical conductivity of an aqueous solution has been possible since the second half of the 19th century [37], and a wide range of conductivity meter models is currently available [38], it is difficult to find a conductivity meter that fully meets all the particular requirements of, for example, the agricultural sector [39]: ease of use, robustness, real-time data transmission, long-term stability, and, possibly, low cost [40]. At end of March 2023, 17,753 articles on Arduino were indexed on Scopus confirming its application in science as a multi-parameter sensor for marine research [41], but also in education [42]. The prototype for conductivity measures here presented fully meets our aims.…”
Section: Discussionmentioning
confidence: 99%
“…Although the measurement of the electrical conductivity of an aqueous solution has been possible since the second half of the 19th century [37], and a wide range of conductivity meter models is currently available [38], it is difficult to find a conductivity meter that fully meets all the particular requirements of, for example, the agricultural sector [39]: ease of use, robustness, real-time data transmission, long-term stability, and, possibly, low cost [40]. At end of March 2023, 17,753 articles on Arduino were indexed on Scopus confirming its application in science as a multi-parameter sensor for marine research [41], but also in education [42]. The prototype for conductivity measures here presented fully meets our aims.…”
Section: Discussionmentioning
confidence: 99%
“…The great advantage of the Arduino microcontroller is that it facilitates designing lowcost, small-scale experiments for verification of diverse physical principles through experiential learning. A recent study [2] has reported the applications of Arduino in different branches of physics to design experiments with new thoughts. Experimental demonstration and analysis of noise [3], large amplitude oscillation [4], and damped oscillation in simple pendulum [5][6][7] are such few examples.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study proposes a method for determining specific heat using the Arduino prototyping platform. This choice is motivated by its reliability, affordability, and widespread availability [24][25][26]. In addition, it combines an analytical methodology suitable for materials in both solid and liquid states, aligning more closely with contemporary demands and students' future careers.…”
Section: Introductionmentioning
confidence: 99%